Implementasi Manajemen Peserta Didik dalam Kaderisasi Siswa Berprestasi di SMK MU Cimerak: Studi Kasus Atlet Voli - Nurhidayat Nurhidayat; Desi Sulistia; Nurjamaludin Nurjamaludin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to analyze the implementation of student management in the volleyball athlete cadre formation process at SMK MU Cimerak, with a focus on talent identification and development strategies, the challenges faced, as well as the impact of the program on sports achievements and student character development. Using qualitative research methods, data was collected through in-depth interviews, participant observation, and document analysis, which was then analyzed using Miles and Huberman's interactive model analysis technique. The research results show that the cadre formation program implemented collaboratively between MTs N 2 Pangandaran and SMK MU Cimerak is effective in developing students' talents and character, despite facing challenges such as limited financial resources and facilities as well as maintaining a balance between sports and academic achievements. This program has succeeded in producing outstanding athletes at the national level and forming students who are disciplined and confident. This research concludes that good student management can increase the effectiveness of cadre formation programs, have a positive impact on developing students' talents and character, and become a model for other schools that wish to develop similar programs.